1998
DOI: 10.1007/s001070050285
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared characterization of Pai wood (Afzelia africana Smith) extractives

Abstract: The major functional groups of the various extractive components recovered from Pai wood using organic solvents and hot water have been identified and assigned by means of Fourier transform infrared analyses. The analyses revealed that the components removed by toluene, found mainly in cell lumina and/or lumina surfaces, were predominantly of non-polar, aliphatic compounds such as fatty acids and their monohydric esters. Gummy substances were also evident as well as minor amounts of materials of aromatic natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 5 publications
1
43
0
5
Order By: Relevance
“…A different study conducted in our laboratory concluded that extractives removed by ethanol and ethanol-toluene were made up of fatty acids, saturated esters, and cyclic polyphenolic compounds. 6,19 Water extracts were mainly made of colorific matter, condensed tannins, and low molecular weight carbohydrates. 6,19 This explains the observed enhanced discoloration when solvent extractions were followed by water extraction.…”
Section: Color Change (⌬E)mentioning
confidence: 99%
See 1 more Smart Citation
“…A different study conducted in our laboratory concluded that extractives removed by ethanol and ethanol-toluene were made up of fatty acids, saturated esters, and cyclic polyphenolic compounds. 6,19 Water extracts were mainly made of colorific matter, condensed tannins, and low molecular weight carbohydrates. 6,19 This explains the observed enhanced discoloration when solvent extractions were followed by water extraction.…”
Section: Color Change (⌬E)mentioning
confidence: 99%
“…Substances such as flavonoids, lignans, and tannins are polyphenolic substances with the natural tendency to greasiness. 6 In their role as antioxidants, they are capable of protecting wood surface against photooxidation. 7 Many woods absorb light beyond 500 nm because of the presence of phenolic substances such as flavonoids, stilbene, lignan, tannin, and quinone.…”
Section: Introductionmentioning
confidence: 99%
“…32 The vibrations appearing further down the field at 896 and 810 cm À1 may have arisen from disubstituted ring stretching and out-of-plane carbon single-bonded hydrogen. 26,30 The FTIR spectrum of PMMA in the frequency range 4000-400 cm À1 (Fig. 2) showed two distinct bands at 2978.4 and 2877.8 cm…”
mentioning
confidence: 99%
“…[24][25][26] The bands appearing at 1271 cm À1 were due to either a carbon single-bonded oxygen stretching vibration or an interaction vibration between carbon single-bonded oxygen stretching and in-plane carbon single-bonded hydroxyl bending in carboxylic acids. 30 The band at 1158 cm À1 may have arisen from the asymmetric stretching of CAOAC in the cellulose and hemicelluloses 26,31 or from saturated fatty acid ester carbon single-bonded oxygen stretching in association with the ester carbonyl. 26,31 Strongintensity bands at 1059 and 1036 cm À1 were essentially in the positions corresponding to those observed in the IR spectra of single cotton fibers.…”
mentioning
confidence: 99%
“…In the sapwood of spotted gum, a decrease of this band's intensity at T 12 can be observed, which indicates a decrease in hydroxyl groups (Ajuong and Breese 1998), possibly removed by water in the waterlogging. For the rose gum, the higher intensity in the sapwood for both times (T 0 andT 12 ) is clear.…”
Section: Chemical Evaluation Of Extractivesmentioning
confidence: 95%